Estimação paramétrica e não-paramétrica em modelos de markov ocultos - Medeiros, Francisco Moisés Cândido de (2010)
In this work we study the Hidden Markov Models with finite as well as general state space. In the finite case, the forward and backward algorithms are considered and the probability of a given observed sequence is computed. Next, we use the EM algorithm to estimate the model parameters. In the general case, the kernel estimators are used and to built a sequence of estimators that converge in L1-norm to the density function of the observable process